IOT transforming crypto currency to end energy crisis in villages of Rajasthan: Project Solar Coin - Bright Keswani, Ruchi Dave, Devesh Bandil (International Journal of Advanced Science and Technology, 2019)
In 21st century when our Govt. is developing smart cities the dream of smart home is the future candy for all the residents as everybody like to experience IT enabled homes. The problem areas in developing such homes and their solutions are varied the best solution can be found out through blockchain IoT development which could lead to a better life. Keywords: IOT, Cryptocurrency, Blockchain,Internet of Things